2003
DOI: 10.1007/s10103-003-0260-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-power GaAlAs laser (660 nm) on bone structure and cell activity: an experimental animal study

Abstract: Low-level laser therapy (LLLT) is increasingly being used in the regeneration of soft tissue. In the regeneration of hard tissue, it has already been shown that the biomodulation effect of lasers repairs bones more quickly. We studied the activity in bone cells after LLLT close to the site of the bone injury. The femurs of 48 rats were perforated (24 in the irradiated group and 24 in the control group) and the irradiated group was treated with a GaAlAs laser of 660 nm, 10 J/cm2 of radiant exposure on the 2nd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
2
21

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 32 publications
7
87
2
21
Order By: Relevance
“…A irradiação do laser de baixa potência tem sido utilizada terapeuticamente para cicatrização de lesões, tratamento de artrite reumatóide, dor musculoesquelética, entre outras aplicações clínicas. Efeitos benéficos são atribuídos à fotoestimulação dos tecidos, como melhora de cicatrização de lesões ulcerativas em indivíduos diabéticos e outros tipos de úlceras 18,19 , além de efeitos analgésicos 20 e antiinflamatórios 21 , estímulo à proliferação de células de diferentes origens 19,[22][23][24] e estimulação do reparo ósseo 18,24 . Os benefícios originados pela radiação laser de baixa potência são gerados pelos mecanismos não-térmicos da interação da luz com os tecidos, resultando em efeitos biomodulatórios por meio de interações fotoquímicas 8,24 .…”
Section: Introductionunclassified
“…A irradiação do laser de baixa potência tem sido utilizada terapeuticamente para cicatrização de lesões, tratamento de artrite reumatóide, dor musculoesquelética, entre outras aplicações clínicas. Efeitos benéficos são atribuídos à fotoestimulação dos tecidos, como melhora de cicatrização de lesões ulcerativas em indivíduos diabéticos e outros tipos de úlceras 18,19 , além de efeitos analgésicos 20 e antiinflamatórios 21 , estímulo à proliferação de células de diferentes origens 19,[22][23][24] e estimulação do reparo ósseo 18,24 . Os benefícios originados pela radiação laser de baixa potência são gerados pelos mecanismos não-térmicos da interação da luz com os tecidos, resultando em efeitos biomodulatórios por meio de interações fotoquímicas 8,24 .…”
Section: Introductionunclassified
“…It is considered a noninvasive, safe technique to stimulate osteogenesis [23,24]. Several previous studies have shown that LLLT could increase both osteoblast and osteoclast activities, together with stimulating the formation of callus and new bone matrix [25][26][27][28]. Of note, LLLT alone as a treatment modality in surgical defects enhanced faster and a greater area of bone formation compared to the PRF treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia et al [24] demonstrated that the LLLT was effective for stimulating bone formation in critical sized defects in the calvaria of rats submitted to ovariectomy. Nicola et al [25] observed that applying LLLT on injured bones increased the bone volume, osteoblasts surface, and mineral apposition rates, suggesting that LLLT increased. Our results confirm the positive bio-stimulatory effect of LLLT, which depends mainly on the ability of the tissue to respond to light energy.…”
Section: Discussionmentioning
confidence: 99%